Peintres témoins de le temps (les); l'age mécanique. (Paris : Hachette, 1959)
Agostini, Tony ; Alde, Yvette ; Ambrogiani, Pierre ; Ardenne, Lucien ; Bellias, Richard ; Bertin, Roger ; Bezombes, Roger ; Bouquillon, Robert ; Brauner, Victor ; Brayer, Yves ; Bret, François ; Buffet, Bernard ; Caillaud, Aristide ; Calder, Alexander ; Capron, Jean-Pierre ; Carzou, Jean ; Cathelin, Bernard ; Chambrin, Jack ; Chape, Jean ; Charlot, Paul ; Ciry, Michel ; Colin, Paul ; Commere, Jean ; Couty, Jean ; Deman, Albert ; Desnoyer, François ; Devoucoux, Robert ; Even, Jean ; Ferro, Gabriel ; Fleury, Lucien ; Fontanarosa, Lucien ; Forissier, Roger ; Foss, Olivier ; Fougeron, André ; Foujita, Tsuguharu ; Gautier, Philippe ; Georgein, Raymond ; Gibert, Lucien ; Gili, Marcel ; Gilioli, Emile ; Gimond, Marcel ; Godard, Gabriel ; Grau-Sala, Emile ; Guastalla, Hélène ; Hambourg, André ; Henry, Pierre ; Hilaire, Camille ; Jacus, Jean ; Labisse, Félix ; Lagru, Dominique ; Lambert-Naudin, Henri ; Colas, Pierre Le ; Guen, Jean Le ; Lelong, Pierre ; Lersy, Roger ; Leygue, Louis ; Lhote, André ; Malaval, Jean ; Masson, Andre ; Mentor, Blasco ; Montané, Roger ; Nakache, Armand ; Noyer, Philippe ; Oudot, Georges ; Pasquier, Francis ; Perot, Luc ; Picasso, Pablo ; Pressmane, Joseph ; Persan, Jean Raffy Le ; Roca, José ; Rodde, Michel ; Sarthou, Maurice ; Savin, Maurice ; Séradour, Guy ; Severini, Gino ; Sicard, Pierre ; Simon, Luc ; Singer, Gérard ; Smith, Francis ; Spitzer, Walter ; Stahly, H.-François ; Strouvé, Sophie ; Taillandier, Roger ; Taslitzky, Boris ; Térechkovitch, Kostia ; Toffoli, Louis ; Ubeda, Agustin ; van Dongen, Kees ; Verdi, Lucien ; Verdier, Maurice ; Vertès, Marcel ; Villon, Jacques ; Antonniucci ; Voyet, Jacques ; Vuillermoz, Louis ; Yankel, Jacques ; Zendel, Gabriel
boek